2000
DOI: 10.1016/s0006-3495(00)76365-x
|View full text |Cite
|
Sign up to set email alerts
|

High Critical Temperature above Tg May Contribute to the Stability of Biological Systems

Abstract: In this study, we characterized the molecular mobility around T(g) in sugars, poly-L-lysine and dry desiccation-tolerant biological systems, using ST-EPR, (1)H-NMR, and FTIR spectroscopy, to understand the nature and composition of biological glasses. Two distinct changes in the temperature dependence of the rotational correlation time (tau(R)) of the spin probe 3-carboxy-proxyl or the second moment (M(2)) were measured in sugars and poly-L-lysine. With heating, the first change was associated with the melting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 56 publications
6
68
0
Order By: Relevance
“…The dependency of M 2 on temperature showed typically one or two transition temperatures where the M 2 decrease became steeper, reflecting motional changes in the immobile component. The lower of these 2 transitions was assigned by Hemminga and co-workers (Buitink et al, 2000) to the onset of significant molecular mobility associated with the glass transition temperature (T g ). The second transition temperature referred to as the critical temperature (T c ) was associated with the crossover from solid-like to liquid-like dynamics where the material first begins to show properties of a viscous liquid (Rössler et al, 1994).…”
Section: Conclusion On Dielectric Analysis Of Glass Transitionmentioning
confidence: 94%
See 1 more Smart Citation
“…The dependency of M 2 on temperature showed typically one or two transition temperatures where the M 2 decrease became steeper, reflecting motional changes in the immobile component. The lower of these 2 transitions was assigned by Hemminga and co-workers (Buitink et al, 2000) to the onset of significant molecular mobility associated with the glass transition temperature (T g ). The second transition temperature referred to as the critical temperature (T c ) was associated with the crossover from solid-like to liquid-like dynamics where the material first begins to show properties of a viscous liquid (Rössler et al, 1994).…”
Section: Conclusion On Dielectric Analysis Of Glass Transitionmentioning
confidence: 94%
“…Component 3 was obtained only under conditions of high temperature and/or high water content, typically well into the rubbery state. In order to monitor the mobility of the immobile protons, the second moment was calculated (Van den Dries et al, 1998;Buitink et al, 2000):…”
Section: Conclusion On Dielectric Analysis Of Glass Transitionmentioning
confidence: 99%
“…Recently, the up-regulation of HSP expression, as well as increases in the levels of protective osmolytes such as trehalose and glycerol, was also found to reduce dehydration-induced stress (Benoit et al, 2010). Since proteins have a considerable effect on the molecular properties of sugar glasses (Slade and Levine, 1991;Bell and Hageman, 1996;Buitink et al, 2000), it seems likely that HSP also has an effect on macromolecular stability in concert with polyhydroxyl compounds in the cytoplasm in a desiccated state. However, little is known about the interplay between HSP and protective osmolytes.…”
Section: Methodsmentioning
confidence: 99%
“…change in slope between above and below the critical ratio) at T/T g equal to 1, if glass transition concept is valid or X w /X b equal to 1, if water activity concept is valid. Buitink et al (2000) measured molecular mobility by ST-EPR and 1 H-NMR, and observed two distinct changes: first one minor shift just close to T g and second abrupt decrease due to solid-like to liquid-like defined as T c . In the case of sugars, T c was observed at 17-35 °C higher than T g and for biological materials it was more than 50 °C.…”
Section: Critical Temperature Concept and Molecular Mobilitymentioning
confidence: 99%